Ako (I)- Ikaw (You) Voices as Counternarrative Structure in Negrense Queer Panalaysayon - Cabayao, Marfy M. (Silliman Journal, 2025)
This paper explores panalaysayon—a Hiligaynon word meaning “account” or “narrative”—as an evolving oral form that attempts to queerize panaysayon, the more established term for storytelling in the Western Visayas Region of the Philippines. In this study, panalaysayon specifically refers to the oral autobiographical narratives of five self-identified queer individuals from the province of Negros Occidental (formerly part of Western Visayas and now under the newly established Negros Island Region). These stories were collected using the life story approach and analyzed through the lens of queer formalism. As a potential literary text, the Negrense queer panalaysayon centers the narrator’s voice and the way their stories are told. A defining feature is the alternating use of ako (I) and ikaw (you) voices, allowing storytellers to express both their internal reflections and how others perceive them. This structure enables them to reclaim agency within narratives where they are often rendered passive or backgrounded. Instead of following conventional narrative arcs with fixed beginning, middle, and end, the panalaysayon reflects an emergent structure. It aligns with the Self-Narrative Model, where narrators select life events and frame them in ways that capture both personal affirmation and struggle. What emerges is a hybrid form—oral, autobiographical, and potentially counternarrative—that demonstrates how queer stories can be told outside dominant, mainstream frameworks. This study does not oppose conventional narrative models but offers panalaysayon as an alternative path within queer storytelling.